Determination of arylsulphatase and phosphatase enzyme activities in soil using screen-printed electrodes modified with multi-walled carbon nanotubes - Stege, Patricia Wanda (2009)
Sustainability of agricultural systems has become an important issue all over the world. The activity of enzymes is potentially an important quality bioindicator in soils. The aim of the present study was to develop a simple and convenient assay to determine the activity of arylsulphatase (AS), acid (ACP) and alkaline phosphatase (ALP) in agricultural soil. The activities of these enzymes were detected using a non-electroactive substrate, which produces an electroactive product. To this end, p-aminophenyl phosphate (pAPP) was used as a substrate which is converted to p-aminophenol (pAP) after enzymatic dephosphorylation; and 4-nitrocatechol sulphate (4-NCS) was used as a substrate for AS activity based on its catalytic effect on the hydrolysis of 4-NCS into 4-nitrocatechol (4-NC). The products of both enzymatic reactions were quantified on carbon-based screen-printed electrodes (SPCEs) modified with carbon nanotubes (CNTs), using Osteryoung square-wave voltammetry (OSWV). The determination of the reaction products allowed more sensitive determination of ALP, ACP and AS activities in soil than that obtained with a spectrophotometric method. This assay also diminishes the generation of waste, which is desirable in green analytical chemistry. The optimization of the analytical procedure in terms of the nature of electrode type, applied potential, pH of solution, and precision of measurements is reported.